Religion in Ashworthy 1958–2011: A Sociology Classic Revisited. (1st November 2013) - Bruce, Steve
Abstract : In A West Country Village: Ashworthy W. M. Williams described the religious life of rural West Devon in the late 1950s. This research updates that study. Data on various indices of Anglican and Methodist involvement show the disappearance of communal conformity, but also increased commitment from the smaller core of committed members. The changed status of the clergy and of the churches is discussed as is their continuing public roles. In a cautionary note, the paper argues that public respect for the secondary functions of the churches should not be mistaken for some widespread 'believing without belonging'.